Political Communication Strategy of Millennial Party Cadres: Building Brand Image in Denpasar - Indah Pratiwi, Nuning; Dananjoyo, Elang; Indra Satria, Wahyu; R. Abdul, Jalloud; Jacob Paul Latupeirissa , Jonathan (Mediator: Jurnal Komunikasi, 2025)
Political communication is a crucial approach in political development, providing a framework for analyzing problems that arise and evolve within the broader processes of political change in a nation. Maintaining a brand image is not limited to trademarks but is also essential for political parties. This study aims to explore the political communication strategies employed by millennial party cadres to build their brand image in Denpasar. The research applies the stonehead audience theory, which categorizes audiences into passive and active groups. A qualitative research method was used, with data collected through observation, interviews, and documentation. Informants were selected using a purposive sampling technique. The findings reveal that the political communication strategy implemented by millennial party cadres was effective, achieving the desired brand image as initially formulated. The study also highlights that these cadres tailored their communication approaches to engage both passive and active audiences. Moreover, it is suggested that the cadres consistently share information and content emphasizing the party's millennial identity to sustain and strengthen its brand image over time.